2012
DOI: 10.1016/j.jhep.2011.08.021
|View full text |Cite
|
Sign up to set email alerts
|

PPARα is down-regulated following liver transplantation in mice

Abstract: Down-regulation of PPARα seemed to be an adaptive response to metabolic alterations following liver transplantation. These results provide novel information to the understanding of the pathogenesis of early post-transplant events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…In addition, hepatic PPARα expression is reported to be associated with ischemia-reperfusion injury. 20 Therefore, strategies based on hepatic PPARα regulation have the potential to improve the prognosis of patients undergoing LT 21 and to expand the organ donor pool, which is in great shortage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hepatic PPARα expression is reported to be associated with ischemia-reperfusion injury. 20 Therefore, strategies based on hepatic PPARα regulation have the potential to improve the prognosis of patients undergoing LT 21 and to expand the organ donor pool, which is in great shortage.…”
Section: Discussionmentioning
confidence: 99%
“…The role of PPAR α has been clarified in several liver diseases. For instance, PPAR α is downregulated in alcoholic liver disease [ 11 , 36 ] as well as after liver transplantation[ 37 ]. Persistent activation of PPAR α ameliorates hepatic steatosis and inflammation in mice but may also induce hepatocarcinogenesis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kurian et al further identified pathways (PPARα and NF-κB) and targets (i.e., IL-1, CXCL1, TIPARP, TRAF6, and TNFRSF1B) that contribute to the onset of EAD by global gene expression profile analysis ( 15 ). Further research has revealed that PPARα is downregulated after LT, which might be an adaptive response to oxidative stress and hepatocellular damage during LT ( 16 ). Moreover, microRNAs and circular RNAs, such as miRNA-122, circFOXN2, and circNEXTIN3, that are expressed in the liver have been found to be potential early predictors of the onset of EAD ( 6 , 7 ).…”
Section: Discussionmentioning
confidence: 99%